Preventive Effect of Muscone against Cisplatin Nephrotoxicity in LLC-PK1 Cells - Hung Manh Phung; Sullim Lee; Ji Hye Hwang; Ki Sung Kang (Biomolecules, 2020)
Cisplatin, one of the most common antitumor agents, is widely applied to treat various cancerous diseases and is included in the World Health Organization Model List of Essential Medicines. Cisplatin therapy is used to treat 10–20% of all cancerous cases, and its cure rate is especially high in testicular cancer (over 90%). However, a major side effect of this anticancer drug is nephrotoxicity, limiting treatment effect and reducing the quality of life in cancer patients. Muscone, an odoriferous constituent of musk, was confirmed to inhibit cisplatin-induced LLC-PK1 kidney proximal tubule cell death in a dose-dependent manner. In term of renal protective mechanism, muscone inhibited cisplatin oxidative toxicity by decreasing reactive oxygen species (ROS) level and stimulating HO-1 expression. Muscone also exerted anti-inflammation effect through inhibition of p38 phosphorylation. Furthermore, muscone mitigated cisplatin-induced apoptosis in LLC-PK1 cells via both intrinsic and extrinsic pathways by inhibiting pro-apoptotic protein Bax expression, and cleaved caspase-3, 7, and 8; and increase of anti-apoptotic protein Bcl-2 level. In addition, the anti-apoptotic effect of muscone also was enhanced by preventing p53 expression and its phosphorylation. Our study showed that muscone may be a potential protective agent against cisplatin-induced nephrotoxicity.